Evaluating the impact of length of time from diagnosis to surgery in patients with unfavourable intermediate‐risk to very‐high‐risk clinically localised prostate cancer. (27th January 2019) - Gupta, Natasha; Bivalacqua, Trinity J.; Han, Misop; Gorin, Michael A.; Challacombe, Ben J.; Partin, Alan W.; Mamawala, Mufaddal K.
Abstract : Objective: To evaluate the impact of length of time from diagnostic biopsy to radical prostatectomy (RP) on oncological outcomes amongst men diagnosed with unfavourable intermediate‐ to very‐high‐risk clinically localised prostate cancer. Patients and methods: We performed a retrospective review of men with a diagnosis of grade group (GG) ≥3 prostate cancer on biopsy, who underwent RP within 6 months of diagnosis, at our institution between 2005 and 2018. We assessed patient demographics, pre‐biopsy disease characteristics, and receipt of neoadjuvant therapy. We categorised time between biopsy and RP into two intervals: <3 and 3–6 months. For each GG, we compared receipt of adjuvant therapy, pathological outcomes at RP (positive surgical margin [PSM], extraprostatic extension [EPE], seminal vesicle invasion [SVI], and lymph node involvement [LNI]), risk of 2‐ and 5‐year biochemical recurrence‐free survival (BCRFS), and 2‐, 5‐, and 10‐year metastasis‐free survival (MFS) between patients who underwent RP at <3 vs 3–6 months after diagnosis. Results: Amongst 2303 men who met the study inclusion criteria, 1244 (54%) had GG 3, 608 (26%) had GG 4, and 451 (20%) had GG 5 disease. In all, 72% underwent RP at <3 months after diagnosis. For each diagnostic GG, there was no significant difference in rates of adjuvant therapy, PSM, EPE, SVI, or LNI in men who had RP at <3 vs 3–6 months after diagnosis. In all, 1568 men had follow‐up after RP of >1 year. For each diagnostic GG, there was no significant difference in 2‐ and 5‐year BCRFS between patients who had RP at <3 vs 3–6 months after diagnosis (GG 3: 78% vs 83% and 69% vs 66%, respectively, P = 0.6; GG 4: 68% vs 74% and 51% vs 57%, respectively, P = 0.4; GG 5: 58% vs 74% and 48% vs 54%, respectively, P = 0.2). Similarly, for each diagnostic GG, there was no significant difference in 2‐, 5‐, and 10‐year MFS between patients who had RP at <3 vs 3–6 months after diagnosis, although we were not able to calculate 10‐year MFS for patients with GG 5 disease due to limited follow‐up in that group (GG 3: 98%, 92%, and 84% vs 97%, 95%, and 91%, respectively, P = 0.4; GG 4: 97%, 90%, and 72% vs 94%, 91%, and 81%, respectively, P = 0.8; GG 5: 89% and 81% vs 91% and 71%, respectively, P = 0.9). Conclusions: Waiting for RP up to 6 months after diagnosis is not associated with adverse outcomes amongst patients with unfavourable intermediate‐ to very‐high‐risk prostate cancer.